Characterization of patients operated on for benign thyroid nodules. Dr. Gustavo Aldereguia Lima Hospital. Cienfuegos, 2014-2019 - José Carlos Aíras Cañizares; José Alberto Puerto Lorenzo; Lidia Torres Aja (Medisur)
Background: benign nodular disease of the thyroid is a frequent reason for medical consultation, its knowledge is of vital importance for the surgeon. Objective: to characterize patients operated on for benign thyroid nodules. Methods: a retrospective case series study was carried out on patients operated on for benign thyroid nodules at the Dr. Gustavo Aldereguia Lima Hospital, over a period of five years. Medical records and biopsy protocols were reviewed; whose data were emptied into a collector model. The variables sex, age, skin color, location of the tumor, as well as its physical and imaging characteristics, were analyzed. In addition, biopsy modalities used, as well as the histological variety, the surgical technique used and the complications. Results: women older than 50 years of age and white skin predominated. The predominant clinical manifestation was the increase in volume in the neck, as well as the presence of single and solid nodules. Likewise, the association of fine-needle aspiration biopsy and paraffin were the most used modalities. Multinodular goiter was the most frequently diagnosed entity. Conclusions: Although benign nodular thyroid disease is not a serious health problem, it is very frequently diagnosed in our environment and surgical treatment is performed, mainly in women over 50 years of age.